POTENSI EKSTRAK BIJI BENGKUANG (PACHYRRHIZUS EROSUS URB.) SEBAGAI LARVASIDA AEDES AEGYPTI L. INSTAR III - Siti Aisah; Eka Sulistyowati; Yasinta Dewi Arum Sari (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2015)
Bengkuang (Pachyrrhizus erosus Urb.) has been known as natural insecticide due to the existence of toxic compound called rotenone. There are some publications on the usage of the P. erosus as pesticide but the affects of seed extract of P. erosus to the larvae of Aedes aegypti based on LC50 and their sub-lethal effects has been unstudied. Accordingly, the research questions were (1) what is LC50 value of the seed extracts? and (2) how does the sub-lethal effect of the seed extract to the larvae derived from their physical morphology and physiology?. The research was done by experimental study using completely random design of five different concentrations (i.e. 0,1%, 0,2%, 3%, 0,4%, 0,5 & 0% as a control) with four replication. Seed extraction followed Harborne (1987). Observation and calculation on the mortality of the larvae were done each six hours in 24 hours. Statistical analyses was done using One Way Anova and LSD test. The result showed that the concentration of the seed extract has significant influence to the mortality of the larvae of A. aegeypti (instar III) with LC50 value on 0,18%. Also, the seed extract caused morphological damages on some parts of the larval body such as head (chepal), chest (thorax), stomach (abdomen), anal gill and loss of hairs on the side of the body. The dead larvae always could be found on the bottom of substrate. The movement of the larvae tend to deliberate after six hours up to 24 hours. Based on the research result, we assume that the seed extract of P. erosus has a potential role as a natural insecticide especially on the larvae of Aedes aegypty (instar III).